Stripped carbon nanotube, positive electrode slurry, positive electrode plate, secondary battery and electric equipment

By activate the carbon nanotubes in alkaline solution, a microporous structure is formed, which solves the problem of poor conductivity of the positive electrode material of lithium-ion batteries and improves the charging and discharging performance and cycle stability of the battery.

CN119461346APending Publication Date: 2025-02-18XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411853839.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The electronic conductivity of the positive electrode materials of existing lithium-ion batteries is poor, resulting in large electron transmission resistance, affecting the battery charge and discharge speed and cycle stability.

Method used

By modifying the carbon nanotubes with alkaline solution as activator, a microporous and mesoporous structure is formed, its specific surface area and conductivity are improved, and it is used as the positive electrode conductor of lithium-ion batteries.

Benefits of technology

It effectively reduces the internal resistance of the battery, improves the charge and discharge performance and cycle stability, and enhances the conductivity and dispersion of the positive electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461346A_ABST
    Figure CN119461346A_ABST
Patent Text Reader

Abstract

The invention discloses a stripped carbon nanotube, positive electrode slurry, a positive electrode plate, a secondary battery and electric equipment. According to the invention, defects and functional groups are introduced to the surface of the carbon nanotube through etching of the activating agent, the surface activity of the carbon nanotube and the contact area of the carbon nanotube and an active material are increased, the stripped carbon nanotube with a rich microporous structure and excellent conductivity is obtained, and the stripped carbon nanotube is used as the positive electrode conductive agent of the lithium ion battery, so that the internal resistance of the battery is effectively reduced, and the service life of the battery is prolonged. And the charge-discharge performance and the cycle stability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a peeled carbon nanotube, a positive electrode slurry, a positive electrode sheet, a secondary battery and an electrical device. Background Art

[0002] Lithium-ion batteries are an indispensable power source in modern electronic devices and are favored for their high energy density, long life and low maintenance requirements. With the continuous advancement of lithium-ion battery technology, a variety of new materials have been developed, such as high-nickel ternary positive electrode materials and silicon-carbon negative electrode materials, aiming to improve the energy density and safety of batteries. The positive electrode materials of lithium-ion batteries play a vital role in battery performance, but existing positive electrode materials have problems such as poor conductivity and large internal resistance, which directly affect the overall performance of the battery. The poor electronic conductivity of the positive electrode material will limit the charging and discharging speed of the battery, especially under high-rate working conditions. Insufficient electronic conductivity leads to greater resistance to electron transmission inside the positive electrode material, resulting in a decrease in effective potential, thereby reducing the number of available lithium ions and affecting the specific capacity and charge and discharge efficiency of the battery. Internal resistance includes the electronic internal resistance and ionic internal resistance of the material. Large electronic internal resistance leads to slow electron transmission, affecting the charge and discharge performance of the battery; large ionic internal resistance leads to slow diffusion of lithium ions inside the positive electrode material, increasing the polarization of the battery and reducing the power output and cycle stability of the battery.

[0003] The use of conductive agents directly affects the conductivity of positive electrode materials. Currently, the commonly used conductive agents in positive electrode materials of lithium-ion batteries include carbon black, conductive graphite, carbon nanotubes, graphene, etc. Carbon nanotubes have a one-dimensional fibrous structure and can form a continuous conductive network in the electrode active material, improving battery capacity, rate performance, battery cycle life, and reducing battery interface impedance. However, due to the strong van der Waals force between carbon nanotubes, they are easy to form agglomerations, resulting in poor dispersion in the electrode material, affecting the conductivity of the battery; the contact area between carbon nanotubes and active materials is limited, which affects their conductivity; during the battery charging and discharging process, the conductive network formed by carbon nanotubes collapses due to the change in the volume of the active material, making it difficult to maintain a stable structure. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0005] To this end, embodiments of the present invention provide a peeled carbon nanotube, a positive electrode slurry, a positive electrode sheet, a secondary battery, and an electrical device.

[0006] In a first aspect, the present invention provides a peeled carbon nanotube obtained by modifying the carbon nanotube with an activator, wherein the activator is an alkaline solution.

[0007] Furthermore, the carbon nanotubes treated by the activating agent are peeled off to form microporous and mesoporous structures.

[0008] Furthermore, the mass concentration of the alkaline solution is within 50%.

[0009] Furthermore, the solute of the alkaline solution includes at least one of KOH, NaOH, Na2CO3, K2CO3, and NaHCO3.

[0010] Furthermore, the modification treatment of carbon nanotubes with an activator includes: adding carbon nanotubes to the activator, ultrasonically stirring and drying to obtain a mixed solid substance; grinding and calcining the mixed solid substance, washing with water to neutrality, filtering and drying to obtain peeled carbon nanotubes.

[0011] In a second aspect, the present invention proposes a positive electrode slurry, comprising a positive electrode active material, a binder and a conductive agent, wherein the conductive agent comprises the exfoliated carbon nanotubes proposed in the first aspect.

[0012] Furthermore, the conductive agent also includes one or more of carbon black, Ketjen black, carbon nanofiber, conductive graphite, and graphene.

[0013] In a third aspect, the present invention provides a positive electrode sheet, which is obtained by coating the positive electrode slurry provided in the second aspect on a positive electrode current collector, followed by drying and rolling.

[0014] In a fourth aspect, the present invention provides a secondary battery, which is manufactured by stacking or winding a negative electrode sheet, a separator, and the positive electrode sheet provided in the third aspect.

[0015] In a fifth aspect, the present invention provides an electrical device comprising the secondary battery provided in the fourth aspect.

[0016] Compared with the prior art, the beneficial effects of the present invention are:

[0017] The present invention introduces defects and functional groups on the surface of carbon nanotubes through activator etching, thereby increasing its surface activity and the contact area with active materials, and obtaining peeled carbon nanotubes with rich microporous structure and excellent conductivity. The peeled carbon nanotubes are used as positive electrode conductive agents for lithium ion batteries, which effectively reduces the internal resistance of the battery and improves the charge and discharge performance and cycle stability of the battery.

[0018] During the etching process of carbon nanotubes in the present invention, the gas generated helps to interrupt the van der Waals force between the carbon nanotubes and effectively reduce agglomeration, thereby making the peeled carbon nanotubes more dispersed in the positive electrode material, forming a uniformly dispersed conductive network, which helps to maintain the stability of the positive electrode material during the cycle and improve the cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0020] Figure 1 A diagram showing the preparation process of peeling off carbon nanotubes of the present invention;

[0021] Figure 2 is the nitrogen adsorption-desorption curve of the initial carbon nanotubes;

[0022] Figure 3 This is a nitrogen adsorption-desorption curve of the peeled carbon nanotubes prepared in Example 1. DETAILED DESCRIPTION

[0023] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0024] The peeled carbon nanotubes, positive electrode slurry, positive electrode sheet, secondary battery and electrical equipment proposed by the present invention are described below with reference to the accompanying drawings.

[0025] The peeled carbon nanotubes are obtained by modifying the carbon nanotubes with an activator, that is, modifying the ordinary initial carbon nanotubes to obtain the peeled carbon nanotubes. Figure 1 As shown, the processing process includes the following steps:

[0026] (a) adding carbon nanotubes to an activator, stirring with ultrasonic waves, and drying to obtain a mixed solid material;

[0027] (b) grinding and calcining the mixed solid material, washing with water until neutral, filtering and drying to obtain the exfoliated carbon nanotubes.

[0028] In step (a), the activator is an alkaline solution, and the mass concentration of the alkaline solution is within 50%. When the mass concentration of the alkaline solution is too high, the etching degree is too high, which will cause the original tubular structure of the carbon nanotubes to be completely destroyed and its conductivity will also be reduced.

[0029] In some embodiments, the solute of the alkaline solution includes at least one of KOH, NaOH, Na2CO3, K2CO3, and NaHCO3.

[0030] Ultrasonic stirring allows the carbon nanotubes to be evenly dispersed in the activator and can also accelerate the activation rate. The time of ultrasonic stirring is set according to specific circumstances.

[0031] After the ultrasonic treatment is completed, the mixed solution is placed in a blast drying oven to dry to obtain a mixed solid substance. The drying temperature of the mixed solution in the blast drying oven is 75 to 85° C., and the drying time is 12 to 24 hours. The purpose of the drying process is to dry and remove the moisture in the mixed solution. It can be understood that the appropriate drying temperature and drying time are selected according to the specific situation.

[0032] In step (b), the mixed solid material obtained in step (a) is fully ground and placed in a tube furnace for calcination at 700-800° C. for 2-4 hours. After the temperature of the tube furnace is reduced to room temperature, the material is taken out, repeatedly washed with water until neutral, filtered and dried to obtain the peeled carbon nanotubes. It is understood that the appropriate calcination temperature and calcination time are selected according to the specific situation.

[0033] In the present invention, the carbon nanotubes are effectively peeled off by activator treatment to form rich micropores and mesoporous structures, thereby increasing their specific surface area and conductivity. During the activation process, gases such as CO, CO2 and H2 may be generated and released, which help to interrupt the van der Waals forces between the carbon nanotubes and reduce agglomeration, thereby making the peeled carbon nanotubes more dispersed in the positive electrode material, forming a uniformly dispersed conductive network, and helping to maintain the stability of the positive electrode material during the cycle. The activator activation process can introduce oxygen-containing functional groups on the surface of the carbon nanotubes, which can improve the compatibility of the carbon nanotubes with the electrolyte, thereby improving their performance in the battery.

[0034] The positive electrode active material, the binder, the conductive agent and the solvent are mixed to form a positive electrode slurry, wherein the conductive agent includes the exfoliated carbon nanotubes prepared by the present invention, and the solvent can be N-methylpyrrolidone.

[0035] In some embodiments, the conductive agent further comprises one or more of carbon black, Ketjen black, carbon nanofiber, conductive graphite, and graphene.

[0036] The specific type of positive electrode active material is not subject to specific restrictions and can be selected according to needs. As an example, the positive electrode active material may include but is not limited to lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4), pyrophosphate iron (Li2FeP2O7), lithium cobalt oxide (LiCoO2), spinel lithium manganese oxide (LiMn2O4), spinel nickel lithium manganese oxide (LiNi 0.5 Mn 1.5O4), layered lithium manganese oxide (LiMnO2), lithium nickel oxide (LiNiO2), lithium niobate (LiNbO2), lithium ferrite (LiFeO2), lithium magnesium oxide (LiMgO2), lithium calcium oxide (LiCaO2), lithium copper oxide (LiCuO2), lithium zinc oxide (LiZnO2), lithium molybdate (LiMoO2), lithium tantalate (LiTaO2), lithium tungstate (LiWO2), vanadium oxide, sulfur oxide, silicate oxide, and their respective modified compounds. These materials can be used alone or in combination of two or more.

[0037] The binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0038] The positive electrode slurry is coated on the positive electrode current collector, and after drying, rolling and other processes, the positive electrode sheet can be obtained. The negative electrode sheet, the separator and the obtained positive electrode sheet are stacked or wound to form a secondary battery.

[0039] The present invention is described below in conjunction with specific examples. The test materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0040] Example 1

[0041] Preparation of peeled carbon nanotubes:

[0042] 20g of carbon nanotubes were added to 60mL of a 15% KOH solution, and ultrasonically stirred for 2h. The mixed solution was then placed in a blast drying oven at 80°C and dried for 20h to obtain a mixed solid. The mixed solid was then taken out and fully ground, placed in a tubular furnace, and calcined for 2h at 750°C in a nitrogen atmosphere. When the temperature dropped to room temperature, the material was taken out and repeatedly washed with water until neutral, and then filtered and dried to obtain the peeled carbon nanotubes.

[0043] Preparation of cathode slurry:

[0044] 96.5 parts by mass of lithium iron phosphate, 1 part by mass of SuperP, and 0.5 parts by mass of peeled carbon nanotubes were added to 2 parts by mass of 5%wt PVDF glue, and mixed and stirred at a speed of 500rpm for 3h, and then the solid content of the slurry was adjusted and controlled to 61% and the viscosity was 7000-10000mPa.s using solvent N-methylpyrrolidone. Finally, high-speed mixing was carried out at a speed of 3000rpm for 30min, and after vacuum defoaming, a positive electrode slurry with a solid content of 61%, a viscosity of 7000-10000mPa.s and good fluidity was obtained.

[0045] Preparation of lithium-ion batteries:

[0046] The positive electrode slurry is evenly coated on the carbon-coated aluminum foil by a high-speed coating machine, and the positive electrode sheet is manufactured by drying and rolling. It is then stacked with the graphite negative electrode sheet to form a soft-pack battery for electrochemical performance evaluation.

[0047] Example 2

[0048] Preparation of peeled carbon nanotubes:

[0049] 20g of carbon nanotubes were added to 60mL of a 20% KOH solution, and ultrasonically stirred for 2h. The mixed solution was then placed in a blast drying oven at 80°C and dried for 20h to obtain a mixed solid. The mixed solid was then taken out and fully ground, placed in a tubular furnace, and calcined for 2h at 750°C in a nitrogen atmosphere. When the temperature dropped to room temperature, the material was taken out and repeatedly washed with water until neutral, and then filtered and dried to obtain the peeled carbon nanotubes.

[0050] Preparation of cathode slurry:

[0051] 96.5 parts by mass of lithium iron phosphate, 1 part by mass of SuperP, and 0.5 parts by mass of peeled carbon nanotubes were added to 2 parts by mass of 5%wt PVDF glue, and mixed and stirred at a speed of 500rpm for 3h, and then the solid content of the slurry was adjusted and controlled to 61% and the viscosity was 7000-10000mPa.s using solvent N-methylpyrrolidone. Finally, high-speed mixing was carried out at a speed of 3000rpm for 30min, and after vacuum defoaming, a positive electrode slurry with a solid content of 61%, a viscosity of 7000-10000mPa.s and good fluidity was obtained.

[0052] Preparation of lithium-ion batteries:

[0053] The positive electrode slurry is evenly coated on the carbon-coated aluminum foil by a high-speed coating machine, and the positive electrode sheet is manufactured by drying and rolling. It is then stacked with the graphite negative electrode sheet to form a soft-pack battery for electrochemical performance evaluation.

[0054] Example 3

[0055] Preparation of peeled carbon nanotubes:

[0056] 20g of carbon nanotubes were added to 60mL of a 30% KOH solution, and ultrasonically stirred for 2h. The mixed solution was then placed in a blast drying oven at 80°C and dried for 20h to obtain a mixed solid. The mixed solid was then taken out and fully ground, placed in a tubular furnace, and calcined for 2h at 750°C in a nitrogen atmosphere. When the temperature dropped to room temperature, the material was taken out and repeatedly washed with water until neutral, and then filtered and dried to obtain the peeled carbon nanotubes.

[0057] Preparation of cathode slurry:

[0058] 96.5 parts by mass of lithium iron phosphate, 1 part by mass of SuperP, and 0.5 parts by mass of peeled carbon nanotubes were added to 2 parts by mass of 5%wt PVDF glue, and mixed and stirred at a speed of 500rpm for 3h, and then the solid content of the slurry was adjusted and controlled to 61% and the viscosity was 7000-10000mPa.s using solvent N-methylpyrrolidone. Finally, high-speed mixing was carried out at a speed of 3000rpm for 30min, and after vacuum defoaming, a positive electrode slurry with a solid content of 61%, a viscosity of 7000-10000mPa.s and good fluidity was obtained.

[0059] Preparation of lithium-ion batteries:

[0060] The positive electrode slurry is evenly coated on the carbon-coated aluminum foil by a high-speed coating machine, and the positive electrode sheet is manufactured by drying and rolling. It is then stacked with the graphite negative electrode sheet to form a soft-pack battery for electrochemical performance evaluation.

[0061] Example 4

[0062] Preparation of peeled carbon nanotubes:

[0063] 20g of carbon nanotubes were added to 60mL of a 40% KOH solution, and ultrasonically stirred for 2h. The mixed solution was then placed in a blast drying oven at 80°C and dried for 20h to obtain a mixed solid. The mixed solid was then taken out and fully ground, placed in a tubular furnace, and calcined for 2h at 750°C in a nitrogen atmosphere. When the temperature dropped to room temperature, the material was taken out and repeatedly washed with water until neutral, and then filtered and dried to obtain the peeled carbon nanotubes.

[0064] Preparation of cathode slurry:

[0065] 96.5 parts by mass of lithium iron phosphate, 1 part by mass of SuperP, and 0.5 parts by mass of peeled carbon nanotubes were added to 2 parts by mass of 5%wt PVDF glue, and mixed and stirred at a speed of 500rpm for 3h, and then the solid content of the slurry was adjusted and controlled to 61% and the viscosity was 7000-10000mPa.s using solvent N-methylpyrrolidone. Finally, high-speed mixing was carried out at a speed of 3000rpm for 30min, and after vacuum defoaming, a positive electrode slurry with a solid content of 61%, a viscosity of 7000-10000mPa.s and good fluidity was obtained.

[0066] Preparation of lithium-ion batteries:

[0067] The positive electrode slurry is evenly coated on the carbon-coated aluminum foil by a high-speed coating machine, and the positive electrode sheet is manufactured by drying and rolling. It is then stacked with the graphite negative electrode sheet to form a soft-pack battery for electrochemical performance evaluation.

[0068] Example 5

[0069] Preparation of peeled carbon nanotubes:

[0070] 20g of carbon nanotubes were added to 60mL of a 50% KOH solution, and ultrasonically stirred for 2h. The mixed solution was then placed in a blast drying oven at 80°C and dried for 20h to obtain a mixed solid. The mixed solid was then taken out and fully ground, placed in a tubular furnace, and calcined for 2h at 750°C in a nitrogen atmosphere. When the temperature dropped to room temperature, the material was taken out and repeatedly washed with water until neutral, and then filtered and dried to obtain the peeled carbon nanotubes.

[0071] Preparation of cathode slurry:

[0072] 96.5 parts by mass of lithium iron phosphate, 1 part by mass of SuperP, and 0.5 parts by mass of peeled carbon nanotubes were added to 2 parts by mass of 5%wt PVDF glue, and mixed and stirred at a speed of 500rpm for 3h, and then the solid content of the slurry was adjusted and controlled to 61% and the viscosity was 7000-10000mPa.s using solvent N-methylpyrrolidone. Finally, high-speed mixing was carried out at a speed of 3000rpm for 30min, and after vacuum defoaming, a positive electrode slurry with a solid content of 61%, a viscosity of 7000-10000mPa.s and good fluidity was obtained.

[0073] Preparation of lithium-ion batteries:

[0074] The positive electrode slurry is evenly coated on the carbon-coated aluminum foil by a high-speed coating machine, and the positive electrode sheet is manufactured by drying and rolling. It is then stacked with the graphite negative electrode sheet to form a soft-pack battery for electrochemical performance evaluation.

[0075] Example 6

[0076] Preparation of peeled carbon nanotubes:

[0077] 20g of carbon nanotubes were added to 60mL of a 15% KOH solution, and ultrasonically stirred for 2h. The mixed solution was then placed in a blast drying oven at 80°C and dried for 20h to obtain a mixed solid. The mixed solid was then taken out and fully ground, placed in a tubular furnace, and calcined for 2h at 750°C in a nitrogen atmosphere. When the temperature dropped to room temperature, the material was taken out and repeatedly washed with water until neutral, and then filtered and dried to obtain the peeled carbon nanotubes.

[0078] Preparation of cathode slurry:

[0079] 96.5 parts by mass of lithium iron phosphate, 0.5 parts by mass of SuperP, and 1 part by mass of peeled carbon nanotubes were added to 2 parts by mass of 5%wt PVDF glue, and mixed and stirred at a speed of 500rpm for 3h, and then the solid content of the slurry was adjusted and controlled to 61% and the viscosity was 7000-10000mPa.s using solvent N-methylpyrrolidone. Finally, high-speed mixing was carried out at a speed of 3000rpm for 30min, and after vacuum defoaming, a positive electrode slurry with a solid content of 61%, a viscosity of 7000-10000mPa.s and good fluidity was obtained.

[0080] Preparation of lithium-ion batteries:

[0081] The positive electrode slurry is evenly coated on the carbon-coated aluminum foil by a high-speed coating machine, and the positive electrode sheet is manufactured by drying and rolling. It is then stacked with the graphite negative electrode sheet to form a soft-pack battery for electrochemical performance evaluation.

[0082] Comparative Example 1

[0083] Preparation of peeled carbon nanotubes:

[0084] 20g of carbon nanotubes were added to 60mL of a 60% KOH solution, and ultrasonically stirred for 2h. The mixed solution was then placed in a blast drying oven at 80°C and dried for 20h to obtain a mixed solid. The mixed solid was then taken out and fully ground, placed in a tubular furnace, and calcined for 2h at 750°C in a nitrogen atmosphere. When the temperature dropped to room temperature, the material was taken out and repeatedly washed with water until neutral, and then filtered and dried to obtain the peeled carbon nanotubes.

[0085] Preparation of cathode slurry:

[0086] 96.5 parts by mass of lithium iron phosphate, 1 part by mass of SuperP, and 0.5 parts by mass of peeled carbon nanotubes were added to 2 parts by mass of 5%wt PVDF glue, and mixed and stirred at a speed of 500rpm for 3h, and then the solid content of the slurry was adjusted and controlled to 61% and the viscosity was 7000-10000mPa.s using solvent N-methylpyrrolidone. Finally, high-speed mixing was carried out at a speed of 3000rpm for 30min, and after vacuum defoaming, a positive electrode slurry with a solid content of 61%, a viscosity of 7000-10000mPa.s and good fluidity was obtained.

[0087] Preparation of lithium-ion batteries:

[0088] The positive electrode slurry is evenly coated on the carbon-coated aluminum foil by a high-speed coating machine, and the positive electrode sheet is manufactured by drying and rolling. It is then stacked with the graphite negative electrode sheet to form a soft-pack battery for electrochemical performance evaluation.

[0089] Comparative Example 2

[0090] Preparation of cathode slurry:

[0091] 96.5 parts by mass of lithium iron phosphate, 1 part by mass of SuperP, and 0.5 parts by mass of carbon nanotubes were added to 2 parts by mass of 5%wt PVDF glue, and mixed and stirred at a speed of 500rpm for 3h, and then the solid content of the slurry was adjusted and controlled to 61% and the viscosity was 7000-10000mPa.s using solvent N-methylpyrrolidone. Finally, high-speed mixing was carried out at a speed of 3000rpm for 30min, and after vacuum defoaming, a positive electrode slurry with a solid content of 61%, a viscosity of 7000-10000mPa.s and good fluidity was obtained.

[0092] Preparation of lithium-ion batteries:

[0093] The positive electrode slurry is evenly coated on the carbon-coated aluminum foil by a high-speed coating machine, and the positive electrode sheet is manufactured by drying and rolling. It is then stacked with the graphite negative electrode sheet to form a soft-pack battery for electrochemical performance evaluation.

[0094] Test Example 1

[0095] The initial carbon nanotubes and the peeled carbon nanotubes prepared in Example 1 were subjected to nitrogen adsorption and desorption tests. The test results are as follows: Figure 2 and Figure 3 As shown. Figure 2 and Figure 3 It can be seen that the specific surface area of ​​the peeled carbon nanotubes prepared in Example 1 of the present invention is 568.39 m 2 / g, the specific surface area of ​​the initial carbon nanotubes is 490.1.0m 2 / g, indicating that the specific surface area of ​​the peeled carbon nanotubes obtained after treatment with the activator increases.

[0096] Test Example 2

[0097] The positive electrode sheets and the prepared soft-pack batteries obtained in Examples 1 to 6 and Comparative Examples 1 and 2 were tested for positive electrode sheet resistance, first efficiency, DCR, cycle retention rate, and rate discharge performance. The test results are shown in Table 1 below.

[0098] The positive electrode sheet resistance test method is as follows: take the rolled positive electrode sheet and put it into the resistance tester, set the test pressure to 25MPa, after 15s, start the resistance tester and start measuring the electrode sheet resistance value. After the measurement is completed, read and record the resistance value.

[0099] The DCR test method is: charge at 0.33C constant current and constant voltage to 3.65V, leave for 5 minutes, discharge at 0.33C for 90 minutes and 54 seconds (adjust to 50% SOC), leave for 60 minutes, record the end voltage U1, then discharge at 2C for 10 seconds, record the end voltage U2, DCR = (U1-U2) / I.

[0100] The cycle retention rate test method is: put aside for 10 minutes, charge to 3.65V at 1C constant current and constant voltage, put aside for 5 minutes, and then discharge to 2.5V at 1C constant current, and cycle this charge and discharge process for 600 cycles. First effect = first cycle discharge capacity / first cycle charging capacity.

[0101] The rate discharge performance test method is: 0.33C constant current and constant voltage charge to 3.65V, stand for 5 minutes, and then discharge to 2.5V at 0.33C / 0.5C / 1C / 2C / 3C / 4C respectively.

[0102] Table 1:

[0103]

[0104]

[0105] According to Table 1, we can see that:

[0106] It can be seen from Examples 1-5 that as the KOH concentration increases, the resistance of the positive electrode sheet first decreases and then increases. When the KOH concentration is 30%, the positive electrode sheet resistance is as low as 72.65 N / m, and the electrochemical performance of the corresponding battery cell is also optimal at this time, indicating that the activation of alkaline solution with appropriate concentration has a significant effect on improving the electrochemical properties of carbon nanotubes.

[0107] According to Example 6, when the content of peeled carbon nanotubes in the positive electrode slurry is increased to 1 part by mass, the resistance of the positive electrode sheet is lower than the resistance value in Example 1, and the first efficiency, DCR, cycle retention rate and rate discharge of the battery cell are all improved, which further illustrates that peeling carbon nanotubes helps to improve the conductivity of the positive electrode material and the cycle stability performance of the battery cell.

[0108] It can be seen from Comparative Example 1 that when the concentration of the alkali solution is 60%, the tubular structure of the carbon nanotubes is completely destroyed, resulting in a decrease in their conductive properties.

[0109] It can be seen from Comparative Example 2 that when the conductive agent is changed from peeled carbon nanotubes to carbon nanotubes, the conductivity of the positive electrode and the electrochemical performance of the battery cell are both inferior to those in Example 1, which shows that the peeled carbon nanotubes obtained after activation modification have obvious advantages in improving the conductivity of the positive electrode material and optimizing the electrochemical performance of the battery cell.

[0110] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0111] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0112] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for exfoliating carbon nanotubes, characterized in that: The carbon nanotubes are modified by using an activating agent, wherein the activating agent is an alkaline solution.

2. The peeled carbon nanotube according to claim 1, characterized in that: The carbon nanotubes treated by the activating agent are peeled off to form microporous and mesoporous structures.

3. The peeled carbon nanotube according to claim 1, characterized in that: The mass concentration of the alkaline solution is within 50%.

4. The peeled carbon nanotube according to claim 1, characterized in that: The solute of the alkaline solution includes at least one of KOH, NaOH, Na2CO3, K2CO3, and NaHCO3.

5. The peeled carbon nanotube according to claim 1, characterized in that: The modification treatment of carbon nanotubes by using an activator comprises: Adding carbon nanotubes to an activator, stirring with ultrasound and then drying to obtain a mixed solid material; The mixed solid material is ground and calcined, then washed with water until neutral, filtered and dried to obtain the exfoliated carbon nanotubes.

6. A positive electrode slurry, characterized in that: The invention comprises a positive electrode active material, a binder and a conductive agent, wherein the conductive agent comprises the peeled carbon nanotube according to any one of claims 1 to 5.

7. The positive electrode slurry according to claim 6, characterized in that The conductive agent also includes one or more of carbon black, Ketjen black, carbon nanofiber, conductive graphite, and graphene.

8. A positive electrode sheet, characterized in that: The positive electrode slurry is coated on the positive electrode current collector and then dried and rolled.

9. A secondary battery, characterized in that: The negative electrode sheet, the separator and the positive electrode sheet according to claim 8 are manufactured by laminating or winding.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Conductive paste and preparation method and application thereof and battery

    CN110634591A

  • Carbon nanotube, conductive agent, positive plate, battery, battery pack and electric equipment

    CN118619258A

  • Lithium ion multilayer pole piece and preparation method and application thereof

    CN119092644A

  • Graphene-based high-rate lithium ion battery and preparation method therefor

    WO2024212596A1